ANALISIS KOMPETENSI PROFESIONAL GURU BIOLOGI SEKOLAH MENENGAH PERTAMA SEDERAJAT SE KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - Syafrial, Juwita; Lestari, Rena; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The analysis of professional competency biology teachers in throughout junior high school Kepenuhan sub-district Rokan Hulu Regency. The aim of this research was to find out the competency of professional biologi teachers at Junior High School Kepenuhan sub-district in development proffesion. The sample of this research were sigh Biologi teachers class VII from six different Junior High School. The data collection technique used was enguette and analized used descriptive statistic. The research finding showed that the development proffesion aspect had the average persentage 61,01%, comprehending know ledge had the average percentage 72,2%, mastery of academic research materials had average percentage 63,88%. Overall the percentage of professional competency Biologi teachers class VII in Junior High School throughout the Kepenuhan sub-district was 65,69% and categorized as enough.